2022
DOI: 10.1016/j.sjbs.2021.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Exonic variants in multiple myeloma patients associated with relapsed/ refractory and response to bortezomib regimens

Abstract: Novel treatment in multiple myeloma represented by proteasome inhibitors, immunomodulatory drugs and monoclonal antibodies have produced a deep response. However, relapses are possible, and all classes of drugs are refractory to patients. Next-generation sequencing has improved our understanding of the multiple myeloma genome related to drug resistance and has discovered many genomic variants. Therefore, this study was conducted to investigate new variants associated with drug resistance in MM patients who rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The authors also found that the mutational landscape of MM patients in the Iranian population was distinct from other populations, with some specific mutations being more prevalent in Iranian MM patients [58]. The study conducted by Munshi et al identified recurrent mutations commonly seen in multiple myeloma cells.…”
Section: Type Of Samplesmentioning
confidence: 97%
“…The authors also found that the mutational landscape of MM patients in the Iranian population was distinct from other populations, with some specific mutations being more prevalent in Iranian MM patients [58]. The study conducted by Munshi et al identified recurrent mutations commonly seen in multiple myeloma cells.…”
Section: Type Of Samplesmentioning
confidence: 97%
“…Despite prolonging survival times of MM patients, both bortezomib and DARA caused an enhancement in infectious complications thus becoming a life-threatening issue in these patients. The main cause of infection is due to the change in lymphocyte count as well as due to the immunosuppressive effect of the disease [33].…”
Section: Infectious Complicationsmentioning
confidence: 99%
“…Whole exome sequencing on blood samples comparing patients resistant or refractory to both bortezomib and daratumumab were compared with those of patients responding to bortezomib treatment. Numerous significant variants were identified, including in the PIK3CG gene, which has metabolic cellular functions, including as a lipid kinase with altered effects influencing proliferation, angiogenesis, and drug resistance [ 59 ].…”
Section: Gene Expression Signaturesmentioning
confidence: 99%